Healing potentials of oral moringa oleifera leaves extract and tetracycline on methicillin resistant staphylococcus aureus infected wounds of wistar rats (2015)
Summary: The effects of oral dose of aqueous extract of Moringa oleifera and tetracycline antibiotics on cutaneous wounds infected with Staphylococcus aureus were studied in eighteen adult wistar rats (159±31.5g) randomized into three groups: Group A, n = 6, Moringa oleifera-(300 mg/kg). Group B, n = 6, tetracycline (9.4 mg/kg) and Group C, n = 6, Sterile water (control). Six millimetres diameter nape wound, created on each rat under 2% xylazine (5 mg/kg) and 5% ketamine (35 mg/kg), was contaminated with Staphylococcus aureus (108 Colony Forming Unit (CFU). Following infection, treatment was commenced with daily oral dose of test preparations and the wounds were evaluated every other day i.e., day 3, 5, 7, 9, 11, 13 and 15 for wetness (wound exudation), wound edge oedema, hyperaemia, granulation tissues and contraction (diameter). Severe wound exudation existed in all the groups between days 0-3 (p = 1.00). A significantly less (p<0.05) wound exudation was observed at days 3-5 (p = 0.000) and 5-9 (p = 0.003) (Control< Tetracycline <Moringa). Wound edge oedema was significantly less (p<0.05) on days 5-9 (p = 0.000) and 9-15 (p = 0.001) (Control<Moringa<Tetracycline). Hyperaemia was pronounced in all the groups from days 0-3, but became significantly less (p<0.05) at days 5-7 (p = 0.002) and 9-15 (p = 0.001) (Control<Moringa<Tetracycline). A significantly (p<0.05) more wound granulation tissue was observed among the groups at days 5-9 (p = 0.002) and 9-15 (p = 0.001) (Control> Moringa> Tetracycline). Differences in wound diameter was not significant except at days 5-9 (p = 0.013) (Control> Moringa >Tetracycline). Oral doses of Moringa oleifera extract (300mg/kg) and tetracycline (9.4mg/kg) are not effective as antimicrobial or immune-boosting agents to enhance healing of wounds infected with Staphylococcus aureus and hence not recommended for rapid clearance of Staphylococcus aureus infected wounds